Electrical treeing in silicone rubber/organo-montmorillonite - Ahmad, Mohd. Hafizi (2012)
Electrical treeing is one of the main reasons for failure of polymeric materials used in high voltage applications. Treeing is observed to originate at points where impurities, voids, defects, or conducting projections cause excessive local electric field stress in the dielectric. It has been proposed that nanofillers could be employed as an electrical tree inhibitor in polymeric insulating materials. With development of nanotechnology, polymer nanocomposites have drawn much attention, because they are expected to have improved mechanical, thermal and electrical properties over the neat polymer. In this paper, modified nanoclay was used to examine the initiation and propagation of electrical treeing. Effects of electrical treeing on nanocomposites insulating material filled with 1 wt% and 3 wt% of Organo-Montmorillonite (OMMT) were used in this work. The results have shown that electrical tree growth was suppressed in silicone rubber nanocomposites compared with neat silicone rubber which allowed a faster growth of electrical treeing. However, more studies should be carried out with different nanofiller/silicone ratios to see in further enhancements in tree inhibition could be achieved.